Piezoelectricity induced by gaseous molecules adsorbed on ZnO nanotubes - Marana, Naiara L. [UNESP]; Casassa, Silvia; Sambrano, Julio R. [UNESP] (Elsevier, 2022)
DFT simulations were used to investigate the piezoelectric response and changes of ZnO armchair and zigzag nanotubes induced by the adsorption of CO, CO2, and CH4 molecules. It is well known that piezoelectricity can change due to structural deformations that alter the polarizability. This effect can be used to create a gas sensor in which the signal is associated with changes in piezoelectricity intensity caused by adsorption-induced structural deformation. In the case of armchair nanotubes, piezoelectricity appears with the first adsorbed molecule and decreases as molecule concentration increases, reaching a value that is maintained even after the nanotube symmetry is restored. The zigzag's piezoelectricity grows as the concentration of gas molecules increases. In all cases, ZnO nanotubes turn out to be an efficient piezoelectric gas sensor, able to operate at low concentrations due to their high sensibility.
Keywords: DFT; Gas sensor; Nanotube; Piezoelectricity; Toxic gases; ZnO